Disciplinary and pastoral power, food and poverty in late-modernity. (February 2022) - Power, Maddy; Small, Neil
Using a Foucauldian perspective, we explicate the systems of power which shape the lives of women in or at risk of 'food poverty'. We develop a theoretical framework of power for analyses of contemporary food poverty, which we apply to data from focus groups with women on low incomes in two cities in the north of England. Our data underlines the repressive power of the state as well as the broader chronicity of state surveillance. We argue that, while disciplinary and pastoral power may characterise the majority of food banks, alternative logics of mutual aid are evident within some food aid providers. We underline the power of governmental discourse in constituting gendered subjectivities and find that the most potent form of coercion is derived from self-regulation. The article closes by exploring possibilities for praxis via discursive resistance.